Yes she can : 10 stories of hope & change from young female staffers of the Obama White House - Brayton, Jenna (Schwartz & Wade Books, 2019)
"An anthology for young women by young women, featuring stories from ten inspiring young staffers who joined the Obama administration in their 20s with the hope of making a difference"--